‘Group Investigation’: A Cooperative Learning Method for the 10th Grade Students in Speaking English Classroom - Finaty Ahsanah (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
The GI or group investigation is one of the cooperative learning teaching method and little used in English language teaching classroom. In GI students take an active part in establishing their learning goals. A method which ask the students to choose the topic selection, plan, implement, analyze, present, and evaluate. This paper reports a study of implementing the GI method in teaching speaking for the 10th grade students‟ at SMAN 1 Paciran Lamongan. Here, the students still have difficulty in using their English orally. One of the reasons is the lack of confidence they have when they should speak in front of the classroom, so they hope to have a partner to discuss with in order to be more confident to speak up. GI is the right solution to solve the students‟ speaking problem. A descriptive research method is used to get the finding of the study, observation checklist, questionnaire, and practical test are the instruments used to collect the data. The data shows that students are strongly increasing in speaking English from 47.2% to 66.6%. Key words: Speaking ability, The GI method